2016
DOI: 10.11124/jbisrir-2016-003168
|View full text |Cite
|
Sign up to set email alerts
|

Patient, nursing and medical staff experiences and perceptions of the care of people with palliative esophagogastric cancer: a systematic review of the qualitative evidence

Abstract: (2016) Patient, nursing and medical staff experiences and perceptions of the care of people with palliative esophagogastric cancer. JBI Executive summary Background Esophago-gastric cancer is the fifth most common malignancy and its incidence is increasing. The disease is fast paced and five year survival rates are poor. Treatment with palliative intent is provided for the majority of patients but there remains a lack of empirical evidence into the most effective service models to support esophago-gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Exploration of patient experiences in our qualitative study addressed previous gaps in understanding patient and family experiences of advanced oesophageal cancer 5 and QoL trade-offs. 27 The results reflect the challenges of their lived experiences of eating restrictions, concerns over nutrition and diet, and a trial and error approach to combating these. These resonate with other findings 28 and emphasise the need for more structured, proactive multidisciplinary approaches in patients receiving palliative stent therapy.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Exploration of patient experiences in our qualitative study addressed previous gaps in understanding patient and family experiences of advanced oesophageal cancer 5 and QoL trade-offs. 27 The results reflect the challenges of their lived experiences of eating restrictions, concerns over nutrition and diet, and a trial and error approach to combating these. These resonate with other findings 28 and emphasise the need for more structured, proactive multidisciplinary approaches in patients receiving palliative stent therapy.…”
Section: Discussionmentioning
confidence: 75%
“…These resonate with other findings 28 and emphasise the need for more structured, proactive multidisciplinary approaches in patients receiving palliative stent therapy. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies found that high-quality nursing has been utilized to manage patients with cancer. [16][17][18] The implementation of the new advanced cancer nursing role may have contributed to important improvements of QoL for cancer patients with gynaecological, haematological, Head & Neck and upper gastrointestinal cancers. [19] Consistently, outcomes in the current study demonstrated that high-quality nursing efficiently improved QoL and significantly decreased anxiety and depression scale for postoperative patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the mainstay of palliative care research has focused on how care should be offered, including optimal models of delivery, timings for referral, and queries regarding who is in greatest need, and whose role it is to provide this care (18). These questions are particularly pertinent for the advanced oesophago-gastric cancer population, given the scarcity of evidence available to establish which interventions and strategies are most effective in delivering services to advanced oesophago-gastric cancer patients (19) and the limited understanding of the most effective model(s) of care for this clinical population (20).…”
Section: Pre-registrationmentioning
confidence: 99%